In vivo assessment of accuracy of Propex II, Root ZX II, and radiographic measurements for location of the major foramen - Fernanda Garcia Tampelini; Marcelo Santos Coelho; Marcos de Azevêdo Rios; Carlos Eduardo Fontana; Sergio Luiz Pinheiro; Daniel Guimarães Pedro Rocha; Carlos Eduardo da Silveira Bueno (Korean Academy of Conservative Dentistry, 2017)
Objectives The aim of this in vivo study was to assess the accuracy of 2 third-generation electronic apex locators (EALs), Propex II (Dentsply Maillefer) and Root ZX II (J. Morita), and radiographic technique for locating the major foramen (MF). Materials and Methods Thirty-two premolars with single canals that required extraction were included. Following anesthesia, access, and initial canal preparation with size 10 and 15 K-flex files and SX and S1 rotary ProTaper files, the canals were irrigated with 2.5% sodium hypochlorite. The length of the root canal was verified 3 times for each tooth using the 2 apex locators and once using the radiographic technique. Teeth were extracted and the actual WL was determined using size 15 K-files under a × 25 magnification. The Biostat 4.0 program (AnalystSoft Inc.) was used for comparing the direct measurements with those obtained using radiographic technique and the apex locators. Pearson's correlation analysis and analysis of variance (ANOVA) were used for statistical analyses. Results The measurements obtained using the visual method exhibited the strongest correlation with Root ZX II (r = 0.94), followed by Propex II (r = 0.90) and Ingle's technique (r = 0.81; p < 0.001). Descriptive statistics using ANOVA (Tukey's post hoc test) revealed significant differences between the radiographic measurements and both EALs measurements (p < 0.05). Conclusions Both EALs presented similar accuracy that was higher than that of the radiographic measurements obtained with Ingle's technique. Our results suggest that the use of these EALs for MF location is more accurate than the use of radiographic measurements.